2021
DOI: 10.3390/molecules26175141
|View full text |Cite
|
Sign up to set email alerts
|

TRIM28 Selective Nanobody Reduces Glioblastoma Stem Cell Invasion

Abstract: Glioblastoma (GB), is the most common and aggressive malignant primary brain tumour in adults. Intra- and inter-tumour heterogeneity, infiltrative GB cell invasion and presence of therapy-resistant GB stem cells (GSCs) represent major obstacles to favourable prognosis and poor therapy response. Identifying the biomarkers of the most aggressive tumour cells and their more efficient targeting strategies are; therefore, crucial. Recently, transcription factor TRIM28 has been identified as a GB biomarker and, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 65 publications
1
19
0
Order By: Relevance
“…TRIM28, which is a transcription factor involved in gene regulation, is also involved in the proliferation of tumor cells. Recently, in the study by Turnsek et al, TRIM28 was found to be enriched in the tumor core, and was associated with glioma cell invasion in a zebrafish model [ 114 ]. Additionally, recent studies showed that chemokine receptor type 4 (CXCR4) and C-X-C motif chemokine ligand 12 (CXCL12) promoted glioma cells to acquire more invasive phenotypes [ 115 , 116 ].…”
Section: Molecular Mechanisms Of Glioblastoma Cell Invasionmentioning
confidence: 99%
“…TRIM28, which is a transcription factor involved in gene regulation, is also involved in the proliferation of tumor cells. Recently, in the study by Turnsek et al, TRIM28 was found to be enriched in the tumor core, and was associated with glioma cell invasion in a zebrafish model [ 114 ]. Additionally, recent studies showed that chemokine receptor type 4 (CXCR4) and C-X-C motif chemokine ligand 12 (CXCL12) promoted glioma cells to acquire more invasive phenotypes [ 115 , 116 ].…”
Section: Molecular Mechanisms Of Glioblastoma Cell Invasionmentioning
confidence: 99%
“…Compared to non-GSCs and normal progenitors, GSCs harbor increased oxide synthase-2 (NOS2) activity which induces genes regulating tumor growth and distal spread [272]. GSCs exhibit higher expression of TRIM28, a biomarker for GBM, and anti-TRIM28 treatment inhibited GBM cell invasion and spread both in vitro and in vivo [273]. HOXA5 gene amplification is an independent prognostic factor for worse outcomes in GBM patients [274].…”
Section: Glioma Stem Cellsmentioning
confidence: 99%
“…For instance, an oncogenic role for TRIM37 in glioma progression has been reported since TRIM37 targets proliferation, migration/invasion, and the epithelial–mesenchymal transition (EMT) via the regulation of the PI3K/Akt pathway [ 81 ] ( Figure 2 a and Table 2 ). TRIM28 is overexpressed in gliomas, and its expression inversely correlates with overall survival and progression-free survival [ 82 ]. TRIM24 overexpression is characteristic of gliomas and is required for EGFR activation and for STAT3 recruitment and stabilization, which is important for exerting its oncogenic potential [ 83 , 84 ] ( Figure 2 a and Table 2 ).…”
Section: Trim Proteins In Brain Tumorsmentioning
confidence: 99%
“…Moreover, studies based on a nanobody-based anti-proteome approach revealed that TRIM28 can be employed as a diagnostic marker for distinguishing glioblastomas from lower-grade gliomas [ 102 ]. The effect of the anti-TRIM28 nanobody was more notable on GSC invasion than on differentiated GB cells [ 82 ]. Furthermore, TRIM28 was upregulated in GBM-stem-like cells, glioma tissues and cell lines, compared to normal counterparts.…”
Section: Trim Proteins In Brain Tumorsmentioning
confidence: 99%
See 1 more Smart Citation